Anti-Mold and Water Retention Effects of Extracts of Pomegranate Peel on Pellet Feeds and Their Impact on Biochemical Indicators in Tissues and Organs of Cyprinus carpio var. Jian - Haijing Liu; Miaomiao Wang; Junhao Huang; Jiang Li; Chunyan Zheng; Huan Zhang; Jing Xu; Qihui Yang; Gangfu Chen; Huatao Li (Fishes, 2026)
This research was conducted to evaluate the impacts of pomegranate (Punica granatum L) peel extract (PPE) on the mold growth and moisture content in pellet feeds, as well as the biochemical indicators in tissues and organs of fish. Firstly, six types of pellet feeds were formulated by adding 0% or 0.5% of pomegranate peel powder (PP), petroleum ether extract (PEE), ethyl acetate extract (EAE), ethanol extract (EE), or aqueous extract (AQE) of PP. Moisture content was determined by air-drying 10 g of wet pellet feed from each treatment at 60 °C for 48 h in uniform-sized Petri dishes. Mold growth was evaluated by homogenizing 15 g of 12-week stored pellet feed with 15 mL of purified water, incubating at 25 °C for 4 days, and recording mold growth. The results indicated that PP, PEE, EE, and AQE reduced the mold growth in pellet feeds (p